Time-Frequency Analysis of Power Quality Disturbances via the Transform based Techniques - Murugesan, P.; Prabakaran, S. (International Journal of Engineering and Technology, 2018)
Digital India focuses the increased usage of semiconductor devices. These power electronic devices pollute the electric power in the power system which degrades the quality of power. The polluted power affects not only the generation, transmission and distribution side but also affects the modern equipments of customers. The goal of monitoring non-stationary electric signal is to quantify the transient nature of these signals and to extract the important features, which support the smart integrated monitoring system to activate the protection on time, to provide proper maintenance scheduling and to reduce the economical burden. This paper documents an alternate method of Fourier transform, where different digital signal processing techniques has been used to analyze different power quality events to provide visual examination. Its performance has been analyzed with different time-frequency representation methods like STFT spectrogram, CWT scalogram and DWT multi-resolution technique. The DWT can detect the dynamic changes of the non stationary PQ signal accurately.Â Â